Penetapan Kadar Tanin Daun Rambutan (Nephelium Lappaceum L) Secara Kolorimetri - Dewi Nofita (Journal Pharma Saintika, 2022)
Rambutan (Nephelium lappaceum L) has a number of health benefits. The benefits of rambutan that are good for health cannot be separated from the chemical content in it. One part of the rambutan plant that can be useful for health is the leaves. Based on the qualitative test using FeCl3 reagent showed the presence of tannins. The determination of tannin content was carried out by colorimetry using the standard series method. This method is based on a comparison of the intensity of the color of the sample solution with the color of the standard solution. Based on the research results, the tannin content contained in rambutan leaves is 1.5% w/w.